RESPIRATORY PATHOGENS AND ANTI-INFECTIVE IMMUNITY: PECULIARITIES OF THEIR INTERACTION AND OPPORTUNITIES OF THE TREATMENT WITH TOPICAL BACTERIAL LYSATE - L. R. Selimzyanova; E. А. Promyslova; E. А. Vishneva ("Paediatrician" Publishers LLC, 2013)
The article contains data about etiological characterization of respiratory infections, peculiarities of viruses and bacteria influence on the airway epithelium and human's immune response. The main problems of respiratory infections treatment are considered. The article presents a review of mechanistic studies, efficacy and safety trials of the topical bacterial lysate in acute, recurrent and chronic infection respiratory and otorhinolaryngological diseases in children.